Prevalence and associated risk factors of urinary incontinence and dyspareunia during pregnancy and after delivery. (February 2020) - Novo, Rita; Perez-Rios, Monica; Santiago-Pérez, Maria Isolina; Butler, Haylie; Malvar, Alberto; Hervada, Xurxo
Abstract: Objective: The objective of this study is to estimate the prevalence of dyspareunia and stress urinary incontinence (SUI) during pregnancy and after delivery, in addition to evaluating possible associated risk factors. Study design: A cross-sectional study was conducted in 2016 with the target population being women who had given birth within the previous 12 months (n = 6436) in Galicia (Spain). Information was collected regarding the mother's status 6 months before pregnancy, during pregnancy, at the time of delivery, and at the time of the survey. The prevalence of SUI and dyspareunia were estimated and regression models were performed to identify variables associated with both pathologies. Results: The prevalence of SUI and dyspareunia after delivery were 20.4 % (CI95 %: 19.2–22.0) and 23.4 % (22.3–24.8), respectively. The presence of dyspareunia during pregnancy (adjusted prevalence ratio PR 2.1), breastfeeding (PR 1.2), and having a history of episiotomy (PR 1.3) were all variables associated with the presence of dyspareunia after delivery. SUI after delivery was related to the mother's history of SUI before pregnancy (PR 2.4) and during pregnancy (PR 2.0), as well as having undergone vaginal delivery (PR 2.0). Conclusion: Knowing which factors are associated with the manifestation of SUI and dyspareunia in women after delivery is useful for identifying susceptible or "at risk" patients. These variables should be included in the clinical history of every pregnant woman.